Development and Validation of an Empirical Equation to Predict Wet Fabric Skin Surface Temperature of Thermal Manikins (Journal of Fiber Bioengineering and Informatics, 2018)
Thermal manikins are useful tools to study clothing comfort and environmental ergonomics. The simulation of sweating can be achieved by putting a highly wicking stretchable knit fabric “skin” on top of the manikin. However, the addition of such a fabric skin makes it difficult to accurately measure the skin surface temperature. Moreover, it takes considerable amount of time to measure the fabric skin surface temperature at each test. At present the attachment of temperature sensors to the wet fabric skin is still a challenge. The distance of the sensors to the fabric skin could significantly influence the temperature and relative humidity values of the wet skin surface. Hence, we conducted an intensive skin study on a dry thermal manikin to investigate the relationships among the nude manikin surface temperature, heat losses and the fabric skin surface temperature. An empirical equation was developed and validated on the thermal manikin ‘Tore’ at Lund University. The empirical equation at an ambient temperature 34.0 °C is T_{sk} =34.00-0.0103HL. This equation can be used to enhance the prediction accuracy of wet fabric skin surface temperature and the calculation of clothing evaporative resistance.